Characteristics of Heat Transfer for CO2 Flow Boiling in Mini-channel - Jiang Linlin; Liu Jianhua; Ye Fangping; Zhang Liang; Ding Yang; Wu Hao (Zhileng xuebao)
The experimental and theoretical researches have been carried out to get the flow boiling heat transfer characteristics of CO2 as a refrigerant in horizontal mini-channel. Based on infrared thermal imaging tests and experimental study on heat transfer coefficients, the heat transfer coefficients of refrigerant are analyzed qualitatively and quantitatively in follow conditions: Heat flux: 2-35 kW/m2,Saturation temperature: ﹣10 ℃-15 ℃, mini-channel inner diameter:1mm or 2 mm. Primary conclusions can be drawn from the results of experiments: The increase of heat flux enhances the nucleate boiling heat transfer of refrigerant inside mini-channel, which leads to the remarkable increase of heat transfer coefficient; the heat transfer coefficient doesn’t always monotonely vary with the saturation temperature: when the saturation temperature is high and even close to the critical temperature of CO2, the heat transfer coefficient rises with the increase of saturation temperature; when the saturation temperature is low, the heat transfer coefficient rises with the decline of saturation temperature. Besides, during the heat transfer process, the dryout quality monotonely falls with the rise of saturation temperature.